1992
DOI: 10.1039/p19920003043
|View full text |Cite
|
Sign up to set email alerts
|

Protection of hydroxy groups by silylation: use in peptide synthesis and as lipophilicity modifiers for peptides

Abstract: A survey of a series of organosilyl derivatives of serine and tyrosine has shown that they have a satisfactory stability profile for use in peptide synthesis. Only when alkaline conditions were used did side-reactions appear. A range of stability profiles have been determined from a study of organosilyl derivatised dipeptides under different conditions, giving t4-values for hydrolysis ranging from 41 to 465 min in acid conditions, yet giving long-term stability at pH-values near to neutrality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 7 publications
2
56
1
Order By: Relevance
“…Under the acidic test conditions it was observed that the hydrolytic stability, as measured by the half-life of 4a-d, varies according to: -OSitBuPh 2 >> −OSitHexylMe 2 > −OTIPS ≈ −OSitBuMe 2 and under basic conditions -OTIPS >> −OSitHexylMe 2 > −OSitBuPh 2 > −OSitBuMe 2 . Neither of these trends is consistent with that which is observed for the analogous phenyl ethers [39]. The reason for these disparities is unclear.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Under the acidic test conditions it was observed that the hydrolytic stability, as measured by the half-life of 4a-d, varies according to: -OSitBuPh 2 >> −OSitHexylMe 2 > −OTIPS ≈ −OSitBuMe 2 and under basic conditions -OTIPS >> −OSitHexylMe 2 > −OSitBuPh 2 > −OSitBuMe 2 . Neither of these trends is consistent with that which is observed for the analogous phenyl ethers [39]. The reason for these disparities is unclear.…”
Section: Resultssupporting
confidence: 59%
“…The silyl ethers chosen for this study were trimethylsiloxy (−OSiMe 3 ), tert-butyldimethylsiloxy (−OSitBuMe 2 ), tert-hexyldimethylsiloxy (−OSitHexylMe 2 ), and diphenyl-tert-butylsiloxy (−OSitBuPh 2 ) groups. These different silyl ethers are all commonly used in protecting group chemistry and are known to span across a range of hydrolytic stabilities [23,24,39]. All of the reactions to produce the resulting triarylamines (4b-d, Scheme 1) and their intermediates proceeded smoothly except the coupling of diarylamine 2 with the trimethylsilyl ether of 4-bromophenol (not shown).…”
Section: Resultsmentioning
confidence: 98%
“…Since the trimethylsilyl group is very unstable toward acidic and basic impurities, 29 we also observed partial deprotection at elevated temperatures used in NMRP conditions. In this case, chain transfer and even crosslinking occurred resulting in insoluble products.…”
Section: Resultsmentioning
confidence: 86%
“…429,430 It is typically removed by TBAF but also by 2 M NaOH (aq) EtOH (1:1). It is more acid-stable than TBDMS and stable to the removal of N-Trt, O-Trt, O-TBDMS and Boc.…”
Section: Other Protecting Groupsmentioning
confidence: 99%